Contiguous Multilevel Thoracic Ossification of Ligamentum Flavum in a Young Adult Spine - Tsuyoshi Yamada; Ichiro Torigoe; Kenichiro Sakai; Atsushi Okawa; Yoshiyasu Arai (Case Reports in Orthopedics)
The ossification of the ligamentum flavum (OLF) was characterized by the replacement of the ligamentum flavum by ectopic new bone formation. Although OLF is well known as one of the causes of thoracic myelopathy through the compression of the spinal cord from the posterolateral side, contiguous multilevel OLF is quite a rare cause of myelopathy. Severe ossifications were reported that only present in individuals aged over 25 years. External triggers of OLF might likely be increased as a consequence of biomechanical stress to the effect of posttraumatic ossification. The authors described one rare case of an enormous contiguous multilevel OLF in a 20-year-old female’s thoracic spine after mild back trauma, to the extent that it was misdiagnosed as an old epidural hematoma initially. This female with obesity presented with a 6-month history of progressively worsening dorsal cord disorders. Resection or floating of the enormous OLF could be successfully achieved using O-arm-based navigation, and sensory loss, numbness, and gait disturbance were improved after operation.